Facile synthesis of ZnS quantum dots at room temperature for ultra-violet photodetector applications - Vincent Teng (Chemical Physics Letters, 2020)
Zinc sulfide (ZnS) quantum dots (QDs) were synthesized using a facile, low-cost and environmentally friendly method at room temperature and ambient pressure. The structural, optical and electrical properties of the as-prepared ZnS QDs were investigated. The monodispersed crystalline ZnS QDs with an average size of 3.8 nm has been prepared, an absorption peak at 292 nm in the ultra-violet (UV) range was observed. The maximum responsivity (R) and detectivity (D*) of the ZnS QDs based photodetector under 365 nm UV light illumination were 5.8 A W−1 and 1.97×1013 Jones, respectively, which shows important potential application in UV detection.